The role of the placenta in the initiation of spiral artery remodelling in an early pregnant chimpanzee uterus. (May 2017) - Vercruysse, L.; Carter, A.M.; Pijnenborg, R.
Abstract: Introduction: In this study we evaluated the full extent of placental bed changes (centre to periphery) in a pregnant chimpanzee uterus, kept at the Museum for Central Africa in Tervuren, Belgium. According to placental size the specimen was equivalent to an 8 weeks pregnant human uterus. Methods: Histological sections from central to peripheral tissue blocks of the placental bed were stained to reveal the presence of trophoblast, endothelium, vascular smooth muscle and elastic laminae. As an indicator for early arterial remodelling, we evaluated endothelial nuclear rounding and subendothelial vascular changes within the maternal vasculature in decidua and adjacent inner myometrium. Results: While interstitially invading trophoblasts were present, endovascular trophoblast invasion seemed about to start into one spiral artery outlet at the centre of the placental bed, confirming our previous impression of a later onset of endovascular trophoblast invasion as compared to the human. An early sign of spiral artery remodelling was rounding of the endothelial nuclei. This phenomenon was not related to the local presence of interstitial trophoblast. Discussion: Endothelial nuclear rounding turned out to be a feature of the placental bed as a whole, being significantly less prominent in the adjacent non-placental bed part of the uterus, indicating an effect of the presence of the placenta. The different time-course of early spiral artery remodelling in the chimpanzee as compared to the human may have had a significant impact upon our evolution. Highlights: Spiral artery invasion by endovascular trophoblast has a later onset than in the human. Endothelial nuclear rounding, a sign of early spiral artery remodelling, is more prominent in the placental bed. Vascular muscle continuity and elastica prominence are reduced in the placental bed decidua. Endothelial nuclear rounding is not related to the local presence of interstitial trophoblast. Presence of interstitial trophoblast decreased vascular muscle layering and prominence of myometrial elastica externa.